The Implementation of Project Based Learning Model Through Mini Drama Project in Improving Students’ Speaking Ability in Class X.5 of SMA Negeri 1 Abang The Academic Year 2025/2026 - I Ketut Widiada; Ni Komang Sri Mariati; I Ketut Wiriawan (Syntax Idea, 2026)
This study was conducted because many students still experienced difficulties speaking English fluently and confidently during classroom learning activities. Students often showed low participation, limited vocabulary mastery, inaccurate pronunciation, and fear of making mistakes when speaking English. Therefore, this study aimed to investigate the implementation of the Project-Based Learning model through mini drama projects in improving students’ speaking ability in Class X.5 of SMA Negeri 1 Abang during the academic year 2025/2026. This study employed classroom action research involving 36 students as research subjects. The research was conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. Data were collected through speaking tests, classroom observation, and documentation. The findings showed that the implementation of Project-Based Learning through mini drama projects successfully improved students’ speaking ability. The students’ mean score increased from 66.80 in the pre-test to 76.53 in Cycle I and continued to improve in Cycle II. In addition, students demonstrated better fluency, pronunciation, vocabulary mastery, grammar, comprehensibility, classroom participation, and self-confidence during speaking activities. In conclusion, Project-Based Learning through mini drama projects is an effective learning model for improving students’ speaking ability and encouraging active participation in English classroom interaction.